Relationship between homocysteine and the enzymes involved in its metabolism with cardiovascular disease and other diseases - Arias Morales , Natalia (2020)
OBJECTIVE: This paper presents a literature review, where general characteristics of homocysteine and plasma deregulation possibly involved in various di- seases especially cardiovascular type and the different methods currently used for determining changes and mutations are described, especially type molecular.METHOD: This research was documentary analysis type. The study sample corresponded to scientific lite- rature included in databases such as scientific articles, books, reports and protocols. For the analysis of the information collected basic descriptive statistics were used. RESULTS: We found that about 75% of the collected information to generate this document, dating back 10 years or so ago, so this may be considered an updated information regarding homocysteine source. With this, it is important to note that in Colombia there have been several studies of genetic and molecular basis to the presence of polymorphisms in the HCY related enzy-mes, such information being useful for future research. CONCLUSIONS: Homocysteine is a risk factor that may be associated with cardiovascular diseases, renal, neural, liver, embryonic type, among others. Studies show that there is collected the most prevalent increa- se of homocysteine in men and shows that the concen- tration tends to increase with age. It was evident that regarding the issue of study, there is a greater number of scientific papers document type compared to books, reviews and official reports (WHO), which may indica- te that it is clear constantly updated research and information on homocysteine and alterations genetic.